ChemInform Abstract: Amine—Borane Complexes: Air‐ and Moisture‐Stable Partners for Palladium‐Catalyzed Borylation of Aryl Bromides and Chlorides. Issue 33 (August 2015) - Guerrand, Helene D. S.; Vaultier, Michel; Pinet, Sandra; Pucheault, Mathieu
Abstract Aryl halides are borylated using an amine—borane complex, which is generated prior to the addition of the coupling partners by treating BH3·NH(iPr)2 with HCl followed by deprotonation with (iPr)2NH.